CFD modelling of shell-side asphaltenes deposition in a shell and tube heat exchanger - Emani, S. (American Institute of Physics Inc., 2017)
Asphaltenes are identified as the main cause of crude oil fouling in the shell and tube exchangers. There are occasions where the crude oil flows through the shell side of the heat exchangers and some fouling is reported in the shell side of those heat exchangers. Understanding the fouling phenomena in the shell sides requires the knowledge on the irregular fluid flow paths and most susceptible locations of particles deposition. In the present work, an attempt has been made to investigate the effect of shear stress and surface roughness on shell-side asphaltenes deposition in a shell and tube heat exchanger through Computational Fluid Dynamics approach. The hydrodynamics of asphaltenes particles and the effect of various forces on the asphaltenes deposition on the heat transfer surfaces has been investigated through a Lagrangian based discrete-phase model. From the CFD analysis, the net mass deposition of the asphaltenes particles reduces with an increase in surface roughness from 0 to 0.04 mm and wall shear stress from 0 to 0.04 Pa for flow velocity 1 m/s, respectively. The asphaltenes mass deposition becomes constant with further increase in wall shear stress and surface roughness. © 2017 Author(s).